THE INFLUENCE OF PRICE ON THE DECISION TO PURCHASE PERCARD WHICH IS MEDIATED BY CONSUMER BEHAVIOR - Asrida, Putu Diah; Saputra, I Gede Agus Adi; Nasuhi, Mochammad Chamim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
This research aims to determine the effect of price on the decision to purchase starter cards, by considering the moderation of consumer behavior. Although many studies have highlighted the relationship between price and consumer purchasing decisions, this study explores whether consumer behavioral factors moderate this relationship in the context of the telecommunications industry. The survey method is used to collect data from respondents who are potential starter card users. The data analysis technique used is the t test with the Moderated Regression Analysis interaction test. This test meets the requirements of instrument testing, classical assumption testing, and model suitability testing. Based on the test results, it is known that price has a significant effect on purchasing decisions with a regression coefficient of 0.879 with a significance of 0.004 < 0.05 and consumer behavior has a significant effect on purchasing decisions with a regression coefficient of 0.684 with a significance of 0.013 < 0.05. Meanwhile, price which is moderated by consumer behavior has no significant effect on purchasing decisions with a regression coefficient value of -0.023 and a significance of 0.112 > 0.05. Thus, consumer behavior variables have not been able to moderate the influence of price on purchasing decisions.